The tropical species of the subgenus Pterygotrigla (Pisces: Triglidae: Pterygotrigla) with description of a new species - Richards, William J.; Yato, Takuji (Zootaxa, 2012)
The tropical species of the triglid subgenus Pterygotrigla (Pterygotrigla) are reviewed. Diagnoses, descriptions, and distributions are given for P. ryukyuensis, P. guezei, for two recently described species, P. saumarez and P. gomoni, and one new species. P. cajorarori, described herein. The statuses of the species of the subgenus are discussed and the subgenus is diagnosed. The subgenus lacks a nasal spine and has a short opercular spine, two features that distinguish it from the other two subgenera. The new species, P. cajorarori, has extreme hyperostosis of the head bones and first dorsal fin spines. It has 12+3 pectoral fin rays and is a rare species with few specimens from Japan, Philippines, Australia, and Indonesia.